Analysis of the Structural Configuration and Typical Motion Process of Wheel Leg Composite Variable Displacement and Obstacle Surmounting Robot - Yin Hesheng; Zhang Qiuju; Ning Meng (Jixie chuandong)
Aiming at the characteristics of unstructured environment,a new type of wheel leg compound variable displacement obstacle surmounting robot suitable for unstructured environment is proposed. The moving robot can deform and step across obstacles. This innovation is that the load acting on the robot can be transported to the height difference on the larger surface to achieve a large barrier by the robot through its own deformation and without the aid,such as the completion of cross-step,into the car and a series of actions. In the process of crossing the barrier,the robot can keep the load plane parallel to the ground and the robot has a strong ability to adapt to the environment and the ability to cross the obstacle. The motion performance of the mobile robot in the non-structural environment of the ramp walking,up and down the steps,the more ditch,climb ladder function is mainly analyzed.